Juventudes, coletivos e participação social no processo de descolonização - Chaves, Bruno (2022)
This study aims to provide a contribution on decolonization from a discussion on youth, youth participation and protoganism of youth groups in Paraíba. The methodology was that of projects, carried out a documentary and bibliographic survey, held events with the project population and applied a questionnaire with participating collectives, of the extension project carried out in 2019. The results were related to the capillarity of collectives as spaces for mediation of youth protagonism, as relevant contributions in the discussion about the public sphere, social participation and protagonism, as aspects/themes that are fundamental to discuss youth, as a social category, which in turn activates the claim against the processes of contemporary colonialism around an action of decolonization, through youth protagonism.